Notoginseng Leaf Triterpenes Ameliorates OGD/R-Induced Neuronal Injury via SIRT1/2/3-Foxo3a-MnSOD/PGC-1α Signaling Pathways Mediated by the NAMPT-NAD Pathway. (23rd October 2020) - Xie, Weijie; Zhu, Ting; Zhou, Ping; Xu, Huibo; Meng, Xiangbao; Ding, Tao; Nan, Fengwei; Sun, Guibo; Sun, Xiaobo
Abstract : Background . Cerebral ischemic stroke (CIS) is a common cerebrovascular disease whose main risks include necrosis, apoptosis, and cerebral infarction. But few therapeutic advances and prominent drugs seem to be of value for ischemic stroke in the clinic yet. In the previous study, notoginseng leaf triterpenes (PNGL) from Panax notoginseng stem and leaf have been confirmed to have neuroprotective effects against mitochondrial damages caused by cerebral ischemia in vivo . However, the potential mechanisms of mitochondrial protection have not been fully elaborated yet. Methods . The oxygen and glucose deprivation and reperfusion (OGD/R)-induced SH-SY5Y cells were adopted to explore the neuroprotective effects and the potential mechanisms of PNGL in vitro . Cellular cytotoxicity was measured by MTT, viable mitochondrial staining, and antioxidant marker detection in vitro .Mitochondrial functions were analyzed by ATP content measurement, MMP determination, ROS, NAD, and NADH kit in vitro . And the inhibitor FK866 was adopted to verify the regulation of PNGL on the target NAMPT and its key downstream. Results . In OGD/R models, treatment with PNGL strikingly alleviated ischemia injury, obviously preserved redox balance and excessive oxidative stress, inhibited mitochondrial damage, markedly alleviated energy metabolism dysfunction, improved neuronal mitochondrial functions, obviously reduced neuronal loss and apoptosis in vitro, and thus notedly raised neuronal survival under ischemia and hypoxia. Meanwhile, PNGL markedly increased the expression of nicotinamide phosphoribosyltransferase (NAMPT) in the ischemic regions and OGD/R-induced SH-SY5Y cells and regulated the downstream SIRT1/2-Foxo3a and SIRT1/3-MnSOD/PGC-1 α pathways. And FK866 further verified that the protective effects of PNGL might be mediated by the NAMPT in vitro . Conclusions . The mitochondrial protective effects of PNGL are, at least partly, mediated via the NAMPT-NAD+ and its downstream SIRT1/2/3-Foxo3a-MnSOD/PGC-1 α signaling pathways. PNGL, as a new drug candidate, has a pivotal role in mitochondrial homeostasis and energy metabolism therapy via NAMPT against OGD-induced SH-SY5Y cell injury.